Conversion from calcineurin inhibitors to sirolimus of recipients with chronic kidney graft disease grade III for a period 2003–2011 - Ignjatovic*, Ljiljana Bozidar; Hrvačevic, Rajko; Jovanović, Dragan; Kovačević, Zoran; Vavić, Neven; Rabrenović, Violeta; Tomić, Aleksandar; Aleksić, Predrag; Draškovć-Pavlović, Biljana; Dujić†., Aleksandar; Karan, Željiko; Maksić, Djoko (Vojnosanitetski pregled, 2013)
Background/Aim. Tremendous breakthrough in solid organ transplantation was made with the introduction of calcineurin inhibitors (CNI). At the same time, they are potentially nephrotoxic drugs with influence on onset and progression of renal graft failure. The aim of this study was to evaluate the outcome of a conversion from CNI-based immunosuppressive protocol to sirolimus (SRL) in recipients with graft in chronic kidney disease (CKD) grade III and proteinuria below 500 mg/day. Methods. In the period 2003–2011 24 patients (6 famale and 18 male), mean age 41 ± 12.2 years, on triple immunosuppressive therapy: steroids, antiproliferative drug [mycophenolate mofetil (MMF) or azathiopirine (AZA)] and CNI were switched from CNI to SRL and followe-up for 76 ± 13 months. Nine patients (the group I) had early postransplant conversion after 4 ± 3 months and 15 patients (the group II) late conversion after 46 ± 29 months. During the regular outpatient controls we followed graft function through the serum creatinine and glomerular filtration rate (GFR), proteinuria, lipidemia and side effects. Results. Thirty days after conversion, in all the patients GFR, proteinuria and lipidemia were insignificantly increased. In the first two post-conversion months all the patients had at least one urinary or respiratory infection, and 10 patients reactivated cytomegalovirus (CMV) infection or disease, and they were successfully treated with standard therapy. After 21 ± 11 months 15 patients from both groups discontinued SRL therapy due to reconversion to CNI (10 patients) and double immunosuppressive therapy (3 patients), return to hemodialysis (1 patient) and death (1 patient). Nine patients were still on SRL therapy. By the end of the follow-up they significantly improved GFR (from 53.2 ± 12.7 to 69 ± 15 mL/min), while the increase in proteinuria (from 265 ± 239 to 530.6 ± 416.7 mg/day) and lipidemia (cholesterol from 4.71 ± 0.98 to 5.61 ± 1.6 mmol/L and triglycerides from 2.04 ± 1.18 to 2.1 ± 0.72 mmol/L) were not significant. They were stable during the whole follow-up period. Ten patients were reconverted from SRL to CNI due to the abrupt increase of proteinuria (from 298 ± 232 to 1639 ± 1641/mg day in 7 patients), rapid growth of multiple ovarian cysts (2 patients) and operative treatment of persisted hematoma (1 patient). Thirty days after reconversion they were stable with an insignificant decrease in GFR (from 56.10 ± 28.09 to 47 ± 21 mL/min) and significantly improved proteinuria (from 1639 ± 1641 to 529 ± 688 mg/day). By the end of the follow-up these patients showed nonsignificant increase in the serum creatinine (from 172 ± 88 to 202 ± 91 mmol/L), decrease in GFR (from 56.10 ± 28.09 to 47 ± 21 mL/day) and increased proteinuria (from 528.9 ± 688 to 850 ± 1083 mg/min). Conclusion. In this small descriptive study, conversion from CNI to SRL was followed by an increased incidence of infections and consecutive 25–50% dose reduction in the second antiproliferative agent (AZA, MMF), with a possible influence on the development of glomerulopathy in some patients, which was the major reason for discontinuation of SRL therapy in the 7 (29%) patients. Nine (37.5%) of the patients experienced the greatest benefit of CIN to SRL conversion without serious post-conversion complications. Key words: kidney transplantation; graft survival; kidney failure, chronic; calcineurin; sirolimus; disease progression.